Aquatic Macroinvertebrate Diversity and Water Quality, La Gallega-Morropón Creek, Piura, Peru - Mónica Santa María Paredes-Agurto, Armando Fortunato Ugaz Cherre,, José Manuel Marchena Dioses, and Robert Barrionuevo Garcia (Nature Environment and Pollution Technology)
Freshwater systems are one of the most important natural resources for life. Despite their value, these ecosystems have suffered great impacts caused by human activities, which directly affect the aquatic biota and the quality of water sources. Considering the value of aquatic macroinvertebrates as bioindicators of water quality, the richness, composition, and water quality of La Gallega-Morropón stream, Piura-Peru, were compared. Two field trips were conducted between November 2018 and May 2019 (contemplated wet and dry periods, respectively), performing 4 sampling stations. A total of 1772 individuals of macroinvertebrates were recorded, distributed in 22 families. Psychodidae had an abundance of 670 individuals, followed by morphospecies (Gasteropoda) with 379 individuals, Chironomidae with 275 individuals, and Elmidae with 136 individuals (all indicators of water quality). Finally, the water quality index method: 1) BMWP/Col, presented one station with good (HB1), acceptable (HB2), and critical (HB3 and HB4) quality, while 2) EPT exhibited two stations with good quality (HB3 and HB4), HB1 regular quality and HB2 poor (HB3 and HB4), HB1 regular quality and HB2 poor quality.